Pemikiran Maurice Bucaille Tentang Peristiwa Banjir Dalam Buku The Bible, The Qur’an And Science - Dewi, Harmila; Rahman, Yenni; A, Efiza (Ikhtisar: Jurnal Pengetahuan Islam, 2025)
This research is motivated by Maurice Bucaille's position as an orientalist who tries to compare the wording of the Qur'an with the Bible and Modern Science. Research on this book was conducted to find out how Maurice Bucaille thinks about the story of the flood in the book The Bible, the Qur'an and Science. The type of research used in this study is library research. The data used in this study comes directly from the Qur'an as a reference for verses and the book The Bible, the Qur'an and Science as a reference for Maurice Bucaille's thoughts on the history of the flood. The data collection technique used in this study is the form of documentation, where the presentation of the data focuses on documents in the form of writings, books, journals and pictures as attachments. The results of this study are that according to Maurice Bucaille, the flood was a special punishment sent down to the people of the prophet Noah. This seems inconsistent with the history of the Qur'an where the Qur'an has mentioned that a flood had happened to Pharaoh and his people and had also hit the Saba people.